Systems theory and agile brand management : the educative view of branding - Lies, Jan (New York, NY : Routledge, 2024)
"Brands started out as communication tools to influence the image of companies or products (inside- out thinking) but have developed into channels of social forces. Powerful brands impact not just customer decisions, but also markets and social institutions, such as fashion trends, city life or even social movements. This book explores the implications of Niklas Luhmann's theory of social systems for the theory and practice of agile brand management, in particular highlighting the central role of brand aesthetics and of brands as channels for mutual education between companies and consumers. Since the rise of social media, "perfect" brands have become the mirror of community values as the communities themselves develop brand content. Brands themselves become "living systems" and evolve like systems do. The author introduces systems theory to provide a conceptual framework which integrates the different views of branding: inside-out and outside-in thinking. This Luhmannian theory of branding is discussed against the current background of (western) societies, which are undergoing a broad shift from hard to soft selling within marketing, influenced by social media. The book is not about whether closed systems analysis and discussion can or should replace traditional management, moreover it emphasizes the fruitful insights and demonstrates that the power of management is limited and should be extended by looking at the means of closed systems. This book will be of primary value to scholars with an interest in systems theory and thinking, brand theory and management. The interdisciplinary approach also makes the book a valuable resource for those researching change management, agile management, and sociology"--
Keywords: Product management; Branding (Marketing) -- Moral and ethical aspects; Social media and society; System theory; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Marketing / Research; BUSINESS & ECONOMICS / General